THE EFFECT OF TOTAL QUALITY MANAGEMENT (TQM) ON EMPLOYEE SATISFACTION IN BANK RAKYAT INDONESIA (BRI) MANADO - Bittie, Windy .; Pangemanan, Sifrid S.; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Total Quality Management is a key strategy for maintaining competitive advantage and is a way of managing organizations to improve it is overall effectiveness and performance. Nowadays, there is a lot of company that already implementing Total Quality Management (TQM). But, it is not guarantee that the employee feels satisfied with the management system. This study is aim to know the effect Of Total Quality Management (TQM) on Employee Satisfaction by analyze the Total Quality Management variable. In line with Government policies that provide opportunities to the private sector to move in the business of banking sector. Along with BRI vision to be excellent and credible company supported by competent human resources, the company has undertaken various efforts to maintain its superior position for all products and services also their quality of employee. The researcher analyzes the data based on primary data and secondary data by using SPSS software. The primary data is collected by distributing 80 questionnaires to 80 employee of Bank Rakyat Indonesia (BRI) Manado. Secondary data is collected by reading various books, journal, and browsing the internet. The researcher used Multiple Linear Regression to analyze the data. The result show that there is significant influence to Employee Satisfaction. The researcher recommends for the Company to improve their management quality to increase employee satisfaction. Because if the employee satisfied with their job, it will increase their performance. Keywords: teamwork and cooperation, organizational culture, reward and recognition, employee empowerment, communication